Meeting report of the 37th International Conference on Antiviral Research in Gold Coast, Australia, May 20-24, 2024, organized by the International Society for Antiviral Research - Welch, Stephen R; Bilello, John P; Carter, Kara; Delang, Leen; Dirr, Larissa; Durantel, David; Feng, Joy Y; Gowen, Brian B; Herrero, Lara J; Janeba, Zlatko; Kleymann, Gerald; Lee, Alpha A; et al. (Antiviral research, 2024)
The 37th International Conference on Antiviral Research (ICAR) was held in Gold Coast, Australia, May 20-24, 2024. ICAR 2024 featured over 75 presentations along with two poster sessions and special events, including those specifically tailored for trainees and early-career scientists. The meeting served as a platform for the exchange of cutting-edge research, with presentations and discussions covering novel antiviral compounds, vaccine development, clinical trials, and therapeutic advancements. A comprehensive array of topics in antiviral science was covered, from the latest breakthroughs in antiviral drug development to innovative strategies for combating emerging viral threats. The keynote presentations provided fascinating insight into two diverse areas fundamental to medical countermeasure development and use, including virus emergence at the human-animal interface and practical considerations for bringing antivirals to the clinic. Additional sessions addressed a variety of timely post-pandemic topics, such as the hunt for broad spectrum antivirals, combination therapy, pandemic preparedness, application of in silico tools and AI in drug discovery, the virosphere, and more. Here, we summarize all the presentations and special sessions of ICAR 2024 and introduce the 38th ICAR, which will be held in Las Vegas, USA, March 17-21, 2025.
Keywords: Vaccine Development; vyvíjení léků; farmakoterapie COVID-19; Austrálie; Animals; Antiviral Agents; Drug Discovery; vývoj vakcíny; Australia; lidé; zvířata; COVID-19 Drug Treatment; objevování léků; antivirové látky; COVID-19; Drug Development; Humans